Analyzing the Content of 2nd Secondary School Grade English Language Textbooks in Light of Life Skills in Jordan - Mohammad Bani Amer; Majid Al-Khataybeh (Britain International for Academic Research (BIAR) Publisher, 2022)
This descriptive-analytic study aimed at identifying the included life skills in the content of 2nd secondary school grade English language textbooks in Jordan through a model for classifying life skills. The researchers designed the content analysis card sought to collect data relevant to the study. The findings of the study showed that there is variance in presenting the nine main domains in 2nd secondary school grade English language textbooks. Even in the one domain, there is a variance in presenting the items. The findings indicated that there are 2676 life skills included in 2nd secondary school grade English language textbooks in Jordan; the effective communicative 24.96%, interpersonal relationship 13.57%, decision-making 11.43%, problem-solving 10.61%, self-awareness building 10.54%, creative thinking 7.70%, empathy 7.66%, coping with stress and emotions 7.51%, critical thinking 6.02%. Also, the findings indicated that the effective communication life skills in 2nd secondary school grade English language textbooks in Jordan have the highest percentage.